When Toleration Becomes a Vice: Naming Aristotle's Third Unnamed Virtue. Issue 4 (27th June 2018) - Avramenko, Richard; Promisel, Michael
Abstract: Toleration is lauded as a chief virtue of contemporary liberalism. Without this virtue, it seems, citizens are ill‐equipped to reconcile ethical disagreements appropriately in pluralistic societies. In recent scholarship and practice, however, toleration has undergone significant transformation. The tolerant citizen, we are told, avoids causing the discomfort or pain associated with uncomfortable conversations, criticism, or even difference of opinion. Regrettably, this understanding of toleration hinders rather than facilitates dialogue and conflates pain or discomfort with cruelty. To offer a more viable theoretical grounding for toleration, this article turns to the third unnamed virtue of Aristotle's Nicomachean Ethics. When conceptualized as an Aristotelian moral virtue with vices of both deficiency and excess, it is clear how toleration, taken too far, becomes a vice. Moreover, Aristotle's principles of contextual sensitivity, other‐regarding virtue, and non‐cruel pain constitute a better foundation for restoring toleration as a healthy virtue for liberal citizens.